An ultrastructural study of the brain in fatal Plasmodium falciparum malaria. - Pongponratn, E; Turner, G; Day, N; Phu, N; Simpson, J; Stepniewska, K; Mai, N; Viriyavejakul, P; Looareesuwan, S; Hien, T; Ferguson, D; White, N (2003)
Cerebral malaria (CM) is a major cause of death in severe Plasmodium falciparum malaria. We present quantitative electron microscopic findings of the neuropathologic features in a prospective clinicopathologic study of 65 patients who died of severe malaria in Thailand and Vietnam. Sequestration of parasitized red blood cells (PRBCs) in cerebral microvessels was significantly higher in the brains of patients with CM compared with those with non-cerebral malaria (NCM) in all parts of the brain (cerebrum, cerebellum, and medulla oblongata). There was a hierarchy of sequestration with more in the cerebrum and cerebellum than the brain stem. When cerebral sequestration was compared with the peripheral parasitemia pre mortem, there were 26.6 times more PRBCs in the brain microvasculature than in the peripheral blood. The sequestration index was significantly higher in CM patients (median = 50.7) than in NCM patients (median = 6.9) (P = 0.042). The degree of sequestration of P. falciparum-infected erythrocytes in cerebral microvessels is quantitatively associated with pre-mortem coma.